Dielectric properties of the lithium-titanium ferrite ceramics in a wide frequency range; Technical Physics; Vol. 60, iss. 6 - Surzhikov A. P. Anatoly Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Lysenko E. N. Elena Nikolaevna; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Malyshev A. V. Andrei Vladimirovich (Solid State, 2015)
Title screen